2020
DOI: 10.1007/s10967-020-07215-4
|View full text |Cite
|
Sign up to set email alerts
|

Radon and thoron radiation exposure of the Angolan population living in adobe houses

Abstract: This study investigates radon and thoron activity concentrations in adobe houses of Angola. Activity concentrations were recorded by passive detectors in rainy and dry seasons in 40 dwellings located at three areas with different climatic and geological backgrounds (Cabinda, Huambo, Menongue). Regarding seasonal and spatial variations, radon activity concentrations are higher in the rainy than in the dry season and both radon and thoron levels are the highest in Huambo, the central part of the country. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Few surveys of measuring thoron in dwellings are available worldwide and very few data are available from Africa. Salupeto-Dembo et al [3] reported radon and thoron radiation exposure in the Angolan population living in adobe houses. Chege et al [4] studied radon and thoron in earthen houses in rural Kenya.…”
Section: Jrprmentioning
confidence: 99%
See 1 more Smart Citation
“…Few surveys of measuring thoron in dwellings are available worldwide and very few data are available from Africa. Salupeto-Dembo et al [3] reported radon and thoron radiation exposure in the Angolan population living in adobe houses. Chege et al [4] studied radon and thoron in earthen houses in rural Kenya.…”
Section: Jrprmentioning
confidence: 99%
“…Track densities (NTnP) from the selective monitor for thoron decay products allow estimation of the equilibrium equivalent thoron concentration (EETC) from the following equation: (3) where NB2 is the background track density of CR-39 in the thoron progeny deposition detectors, T is the exposure time, and F TnP is the conversion factor for the thoron progeny deposition detector. From the results of a field survey [19] and the chemical etching conditions, the valuee of F TnP was 6.9 × 10 -2 tracks/cm 2 per Bq/m 3 /hr.…”
Section: Thoron Progeny Monitorsmentioning
confidence: 99%